Geslachtsziekten. - Protestantse Stichting ter bevordering van Verantwoorde Gezinsvorming (PSVG) ('s-Gravenhage : PSVG, 1980)
Fonds Suzan Daniel (FSD)
Fonds Suzan Daniel (FSD)F/96/015
Nederlands
Monografie